Increased risk of cardiovascular disease in Type 1 diabetes: arterial exposure to remnant lipoproteins leads to enhanced deposition of cholesterol and binding to glycated extracellular matrix proteoglycans - Mangat, R.; Su, J.; Lambert, J.; Clandinin, M.; Wang, Y.; Uwiera, R.; Forbes, J.; Vine, D.; Cooper, M.; Mamo, John; Proctor, S. (Diabetes UK, 2011)
Aims: To determine fasting and postprandial metabolism of apolipoprotein B48 (apoB48) remnant lipoproteins in subjects with Type 1 diabetes and the relationship to progressive cardiovascular disease, and to investigate the impact of remnant lipoprotein cholesterol accumulation associated with arterial wall biglycan using a rodent model of Type 1 diabetes. Methods: Normolipidaemic subjects (n = 9) with long-standing Type 1 diabetes (and advanced cardiovascular disease) and seven healthy control subjects were studied. Fasting and postprandial apoB48 concentration was determined following a sequential meal challenge. A rodent model of streptozotocin-induced diabetes was used to investigate the ex vivo retention of fluorescent-conjugated remnants. Binding of remnant lipoproteins to human recombinant biglycan was assessed in vitro. Results: A significantly higher concentration of fasting plasma apoB48 remnants was observed in patients with Type 1 diabetes compared with control subjects. Patients with Type 1 diabetes exhibited a greater total plasma apoB48 area under the curve (AUC) and an increased incremental AUC following a second sequential meal compared with control subjects. The arterial retention of remnants ex vivo and associated cholesterol was increased sevenfold in Type 1 diabetes rats relative to controls. Remnants were shown to bind with significant affinity to human biglycan in vitro and a further 2.3-fold increased binding capacity was observed with glycated biglycan. Remnants were shown to colocalize with both arterial biglycan and glycated matrix proteins in the Type 1 diabetes rodent model.Conclusion: Impaired metabolism of remnant lipoproteins associated with enhanced binding to proteoglycans appears to contribute to the arterial cholesterol deposition in Type 1 diabetes. Our findings support the hypothesis that impaired remnant metabolism may contribute to accelerated progression of atherosclerosis in the hyperglycaemic and insulin-deficient state.